Wear characteristics and degradation mechanism of natural pumice concrete under ice friction during ice flood season. (25th July 2022) - Wang, Xiaoxiao; Feng, Rongrong; Li, Jie; Liu, Shuguang; Yan, Changwang
Highlights: Variation law of wear amount with concrete strength grade, ice pressure, and environment temperature was obtained. Morphology and pore characteristics of ice–wear natural pumice concrete were analyzed. The degradation mechanism of natural pumice concrete worn by ice was revealed. The prediction model of the wear amount of natural pumice concrete under ice wear was established. Abstract: Wear amount of ice on pumice concrete was investigated to understand wear mechanism of natural pumice concrete (NPC) during ice flood season of the Yellow River in China. Sawn NPC is used as the research object in this study. Strength grades (LC20, LC30, and LC40), ice pressure (1–5 KPa), and environment temperature (0 °C to − 20 °C) on the wear amount of natural pumice concrete as well as changes of surface topography and pore structure characteristics of NPC were analyzed with a super–depth–of–field microscope through the anti–ice wear test. Results showed that apertures increase with the increase of the wear amount because pumice aggregate and cementitious material jointly resist liquid pressure and cutting and fatigue wear modes of the NPC are caused by ice. Detached free abrasive particles cause scratches and wear on the surface and gradually form inward cracks, which cause the pore wall to break and result in the increase of apertures. A wear model with concrete strength grade, ice pressure, and environment temperature as variables combined with test data and degradation mechanism is established. The results of this study can provide a theoretical basis for the application of NPC in the Yellow River during ice flood season.